Conversion of syngas to mixed alcohols over K-Mo-S/activated carbon. - Thao, Nguyen Tien; W. Jones, Christopher (Vietnam Journal of Chemistry, 2012)
The present work reported the catalysts were prepared from activated carbon impregnated with K2CO3 and MoOx and investigated for the synthesis of mixed alcohols from syngas. Two catalyst samples have different MoOx loadings of 15 - 30 wt%. The solids were characterized by XRD, SEM, H2-TPR and BET techniques. An increased Mo loading results in a decreased surface area of the solid. After sulfidation with H2S/H2, the catalysts are tested for the synthesis of alcohols from syngas and show a high CO conversion at values of 10-23%. The predominant product is ethanol with the selectivity of 25-45% at typical reaction conditions.